Cultural Social Relationship With The Implementation Of Antenatal Care (ANC) in The Kambaniru Puskesmas Working Area - Uly Agustine; Maria Christina Endang Sukartiningsih (Poltekkes Kemenkes Kupang, 2019)
Background: One of the goals of the Millennium Development Goals (MDG’s) is to improve maternal health. This goal can be achieved by utilizing Antenatal Care (ANC) services for pregnant women. ANC services are examinations of pregnant women during pregnancy to prevent complications or detect early risks of pregnancy and prepare for healthy births. Health services during pregnancy are important for pregnant women and their babies. Many efforts were made in preventing the bad conditions that can occur in pregnant women, one of which is the MCH Revolution conducted by the NTT government to reduce MMR and IMR. The purpose of this study was to evaluate the extent of the success of the Maternal and Child Health Revolution Program in terms of policies, services and community participation in East Sumba Regency. Method: qualitative presented in the form of descriptive description of phenomenology that is giving description about Social Culture linkage with Antenatal Care (ANC) in Work Area of ​​Puskesmas Kambaniru. The selection of participants is done by purposive strategy. Data collection is done by structured interview method. Results: Themes generated in this study are Maternal Knowledge of Pregnancy, Cultural Tradition, Pregnancy Checkup Site, Social Support, and Barrier Factors. Conclusion: The customs of local cultural traditions performed by pregnant women is still done until now one of them is hamayang or sembayang adat tradition. There are still certain restrictions that pregnant women are not allowed to be associated with cultural traditions.